2002
DOI: 10.1051/0004-6361:20011830
|View full text |Cite
|
Sign up to set email alerts
|

A deep Hαsurvey of galaxies in the two nearby clusters Abell 1367 and Coma

Abstract: Abstract. We present a deep wide field Hα imaging survey of the central regions of the two nearby clusters of galaxies Coma and Abell 1367, taken with the WFC at the INT 2.5 m telescope. We determine for the first time the Schechter parameters of the Hα luminosity function (LF) of cluster galaxies. The Hα LFs of Abell 1367 and Coma are compared with each other and with that of Virgo, estimated using the B band LF by Sandage et al. (1985) and a L(Hα) vs. MB relation. Typical parameters of φ * ≈ 10 0.00±0.07 Mpc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
101
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 70 publications
(108 citation statements)
references
References 48 publications
(59 reference statements)
7
101
0
Order By: Relevance
“…2 red points) or from previous observations of 155 optically selected CGCG galaxies by Gavazzi et al (1999Gavazzi et al ( , 2002aGavazzi et al ( ,b, 2006, , Iglesias-Páramo et al (2002), and Cortese et al (2006) (see Fig. 2 blue points).…”
Section: Coma Superclustermentioning
confidence: 71%
“…2 red points) or from previous observations of 155 optically selected CGCG galaxies by Gavazzi et al (1999Gavazzi et al ( , 2002aGavazzi et al ( ,b, 2006, , Iglesias-Páramo et al (2002), and Cortese et al (2006) (see Fig. 2 blue points).…”
Section: Coma Superclustermentioning
confidence: 71%
“…The Hα gas around a galaxy in a cluster suggests a recent or ongoing gas-loss event of the parent galaxy, since the gas is heated by the ambient hot plasma and will eventually get mixed with it. Such extended ionized gas (EIG) was reported in various nearby clusters; in Abell 1367 (e.g., Gavazzi et al 2001a;Iglesias-Páramo et al 2002;Sakai et al 2002;Gavazzi et al 2003a;Sakai et al 2012), in the Virgo cluster (e.g., Kenney & Koopmann 1999;Yoshida et al 2002;Kenney et al 2008;Arrigoni Battaia et al 2012;Kenney et al 2014), in the Coma cluster (e.g., Yagi et al 2007;Yoshida et al 2008;Yagi et al 2010;Yoshida et al 2012;Fossati et al 2012), in Abell 3627 (e.g., Sun et al 2007Sun et al , 2010, and in some distant clusters (e.g.. Abell 851 Yagi et al 2015a). Yagi et al (2010) found 14 EIGs in the central 1 Mpc of the Coma cluster, a nearby rich cluster.…”
mentioning
confidence: 83%
“…Gavazzi et al (2001a) discovered Hα cometary trails coinciding in length and direction with the radio continuum ones. Iglesias-Páramo et al (2002) gives the Hα emitter catalog of the Abell 1367 (including the Coma cluster) using four exposures of 0.5 degree 2 each obtained with the WFC camera attached to the 2.5m William Herschel Telescope (WHT), with a sensitivity of approximately 10 −15.5 erg s −1 cm −2 obtained with one hour exposures per field. The total number of galaxies with Hα in this sensitivity was 41.…”
mentioning
confidence: 99%
“…We have observed 1 square degree of Coma cluster. The images were obtained using the Sloan-Gunn r filter of the WFC (see Iglesias-Páramo et al 2002). The B band magnitudes of the galaxies were obtained from the Godwin et al (1983) catalogue of Coma cluster galaxies.…”
Section: Structural Parameters and Color Distributionmentioning
confidence: 99%